Indiginerds : tales from modern indigenous life - Pete, Alina; Newton, Brit "Holoske"; Spike, 1978-; Mardikian, Hye; Mardikian, Hye (Iron Circus Comics, 2024)
This is an anthology of short memoir comics about modern indigenous life, with some fiction or fictionalized memories mixed in.--Publisher.